Key Strategies to Enhance Team Resilience for NGO Sustainability: A Case of Charity Corps Myanmar - Dan , Mung; Tantasanee, Somchai; Sirirat, Boonyapak (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study discusses ways to improve team resilience in a non-governmental organization operating in a challenging socio-political context: Charity Corps Myanmar. The study employs qualitative techniques to understand the role of transformational leadership, collective efficacy, team familiarity, and organizational practices in ensuring team resilience and organizational sustainability. Using data from interviews and applying thematic analysis shows important gaps in team dynamics and operation practices that reduce resilience. Using Appreciative Inquiry (AI) and SOAR analysis, this work represents a unique synthesis of frameworks in the context of an NGO and new perspectives on resilience building. They will consider your key takeaways on the importance of adaptability, collaboration and structured organizational practice. To foster transformational leaders and enhance team cohesion and operational efficiency, the study recommends implementing structured leadership training programs and improving communication channels. Our findings offer a useful perspective to NGOs working in high-risk contexts and practical strategies to better resist the challenges they face while serving their mission and accomplishing their objectives.